2019
DOI: 10.1021/acs.langmuir.9b02885
|View full text |Cite
|
Sign up to set email alerts
|

Critical and Optimal Wall Conditions for Coalescence-Induced Droplet Jumping on Textured Superhydrophobic Surfaces

Abstract: The effectiveness of coalescence-induced jumping of microdroplets on superhydrophobic surfaces is critical to a wide range of applications such as self-cleaning surfaces, anti-icing/frosting, water harvesting, phase-change heat transfer, and hotspot cooling. Introducing textures on the surfaces can readily enlarge the effective contact angle, while an overlarge texture spacing may unfavorably lead to droplet penetration into the gaps in droplet coalescence processes. To clarify the effect of surface textures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…In general, the formation process of solidified nanoporous CP films can be divided into four steps: (1) formation of the PS droplets, (2) growth and coalescence of the PS droplets, (3) evaporation of the solvent, and (4) removal of the PS components from the solidified film . According to the classical nucleation theory, the formation mechanism of pores in P3HT films can be attributed to the nucleation of PS in a homogeneous mixture and the growth of PS droplets via coalescence, which is driven by the evaporation of the solvent. , Figure b–f illustrates the mechanism through which the pore size of the P3HT thin films changes with shear rate. In the SAPS method, the transport process in the polymer-blend solution is strongly influenced by two types of flow: the capillary flow and shear flow driven by viscous forces (Figure b). The capillary flow gives rise to an interfacial alignment of the PS chains near the top surface of the solution, while the shear flow drives the PS chain alignment in the bulk of the solution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the formation process of solidified nanoporous CP films can be divided into four steps: (1) formation of the PS droplets, (2) growth and coalescence of the PS droplets, (3) evaporation of the solvent, and (4) removal of the PS components from the solidified film . According to the classical nucleation theory, the formation mechanism of pores in P3HT films can be attributed to the nucleation of PS in a homogeneous mixture and the growth of PS droplets via coalescence, which is driven by the evaporation of the solvent. , Figure b–f illustrates the mechanism through which the pore size of the P3HT thin films changes with shear rate. In the SAPS method, the transport process in the polymer-blend solution is strongly influenced by two types of flow: the capillary flow and shear flow driven by viscous forces (Figure b). The capillary flow gives rise to an interfacial alignment of the PS chains near the top surface of the solution, while the shear flow drives the PS chain alignment in the bulk of the solution.…”
Section: Resultsmentioning
confidence: 99%
“…26 According to the classical nucleation theory, the formation mechanism of pores in P3HT films can be attributed to the nucleation of PS in a homogeneous mixture and the growth of PS droplets via coalescence, which is driven by the evaporation of the solvent. 27,28 Figure 2b−f illustrates the mechanism through which the pore size of the P3HT thin films changes with shear rate. In the SAPS method, the transport process in the polymer-blend solution is strongly influenced by two types of flow: the capillary flow 23 and shear flow driven by viscous forces (Figure 2b).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Some researchers combined the wetting state and the impact effect between the liquid bridge and substrate in explaining the effect of the microgeometry array on droplet coalescence jumping. Yin et al reported that with the decrease in the solid fraction (Figure 6f), 50 when the wetting state of the droplet changed from the Cassie state to the partial wetting state, which could ensure the effective impact area and reduce the surface adhesion, the jumping speed could reach the maximum. The effect of the microgeometry array on droplet coalescencejumping behavior changes with the droplet and the geometric parameters of the microgeometry array.…”
Section: ■ Energy Modelsmentioning
confidence: 99%
“…The solid fraction of the textured surface is f s = w 2 / b 2 . Reproduced from ref , copyright 2019, American Chemical Society.…”
Section: Effect Of Superhydrophobic Structurementioning
confidence: 99%
“…Furthermore, by reasonably designing the substrates with nanopillars that show an arrangement density gradient, the coalescence dynamics, such as the final position or adhesion of the coalesced droplets, the coalescence speed, the shape evolution of the coalescing droplets, could be accurately controlled. Besides, heterogeneous superhydrophobic surfaces decorated with many micropatterned pillars have also been designed for achieving coalescence-induced self-jumping of the droplets. The surfaces decorated with nanostripe structures have also been designed to tune the coalescing behaviors, which also belongs to one kind of surface protruding structure when compared to the smooth surfaces . According to the abovementioned studies, it could be learned that the surface microstructure plays an essential role in the regulation of coalescence dynamics.…”
Section: Introductionmentioning
confidence: 99%